The role of cross-functional integration in new product development: differences between incremental and radical innovation projects - Jugend, Daniel [UNESP]; de Araujo, Tiago Ribeiro [UNESP]; Pimenta, Márcio Lopes; Gobbo, José Alcides [UNESP]; Hilletofth, Per (Taylor & Francis, 2018)
The literature on new product development (NPD) contains several studies of management practices involved in different types of innovation. However, few studies focus on how cross-functional integration affects incremental and radical innovation product projects. The purpose of this study is to explore this aspect, from a qualitative perspective, through case studies of four high-tech firms in Brazil. Eight NPD projects were studied. The findings suggest that radical and incremental innovation NPD projects require different management practices in the studied cases. In incremental NPD projects, greater integration efforts may not be necessary. However, the following practices should be adopted in projects involving radical innovation product projects: intense involvement of technical teams, flexibility in the early stages of NPD, and geographical separation between the development team and other departments of the firm. Moreover, the application of these same practices in projects of incremental innovation in NPD may not bring positive results.
Keywords: contingency analysis; cross-functional integration; incremental innovation; new product development; Radical innovation